'Master My Demons': art therapy montage paintings by active-duty military service members with traumatic brain injury and post-traumatic stress. Issue 4 (4th August 2018) - Berberian, Marygrace; Walker, Melissa S; Kaimal, Girija
Abstract : This study involved a thematic analysis of montage paintings and of related clinical records of 240 active-duty military service members collected during their art therapy treatment for traumatic brain injury and underlying psychological health concerns, including post-traumatic stress, at the National Intrepid Center of Excellence, Walter Reed National Military Medical Center, Bethesda, Maryland, USA. Congruent with other research findings, the qualitative analyses of this study suggest that the group art therapy experiences fostered improvement in interpersonal relatedness, hopefulness and gratification for the service members in treatment, aiding in externalisation, progressive exposure and construction of a trauma narrative imperative for recovery. The mixed media nature of the montage painting supported the expression of a range of postcombat symptoms. Results from this study highlighted the complexity of military culture, necessitating a broader scope of analyses for how art therapy helps service members express and communicate their challenges to care providers, peers and family as well as regulate emotion in the short and long term.